2015
DOI: 10.5935/1806-0013.20150040
|View full text |Cite
|
Sign up to set email alerts
|

Nursing practices for pain management in hospitals of a city of Santa Catarina

Abstract: BACKGROUND AND OBJECTIVES:Pain is the fifth vital sign and requires from health professionals specific skills and knowledge for its management. This study aimed at evaluating nursing practices for pain management in hospitals of a city in Southern Brazil. METHODS: This was a cross-sectional and quantitative study carried out by means of a structured questionnaire to evaluate professional characteristics and knowledge about pain in a sample of 418 professionals: 63 nurses and 355 nursing technicians from three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…5 It is observed that acute pain presents as the main complaint reported by patients in emergency and emergency services, highlighting that, of approximately 90% 45% of the patients present the pain symptom related to some specific event. 6 It is also observed that acute pain is the most prevalent in emergency room and emergency room visits. 7 It can be seen that few visits to patients with chronic pain in these places are very few, since they seek care of urgency and emergency, most of the time, when a new acute process of the symptom occurs.…”
Section: Inmentioning
confidence: 99%
See 1 more Smart Citation
“…5 It is observed that acute pain presents as the main complaint reported by patients in emergency and emergency services, highlighting that, of approximately 90% 45% of the patients present the pain symptom related to some specific event. 6 It is also observed that acute pain is the most prevalent in emergency room and emergency room visits. 7 It can be seen that few visits to patients with chronic pain in these places are very few, since they seek care of urgency and emergency, most of the time, when a new acute process of the symptom occurs.…”
Section: Inmentioning
confidence: 99%
“…41 Nursing interventions described in the classification of NIC 13 that had not been identified in the Nursing records of the unit were presented. It is reported that, of these, the group identified that, in addition to the mapped intervention, it performed six (6) other interventions in the nursing practice, which were not being registered. These interventions are shown in figure 1.…”
Section: Inmentioning
confidence: 99%
“…Pain is considered the fifth vital sign and health services must encourage and monitor the professionals regarding the assessment of pain as a vital sign, as well as the use of pain scales. Health services must seek to relieve a suffering that is often manageable (23) . The nurses mentioned some methods used to promote the comfort of the child during a painful crisis: offering a peaceful environment, minimizing the noise, encouraging bed rest, stimulating walking when possible and encouraging hydration.…”
Section: Discussionmentioning
confidence: 99%
“…It shows that the limitation of specific knowledge about methods and scales of pain evaluation can contribute to unnecessary suffering of patients and reduction of quality of life. 16 Another explanation for the result of this research is the need to better understand the numerical verbal scale, since the Nursing team in the fifth-degree pain screening may underestimate it. 17 It is reported that in another study that also assessed pain management before and after the fifth sign implantation showed that the management did not change in the treatment of pain and change in analgesia suggesting that the measurement of pain as the fifth vital sign does not change the management of pain routinely.…”
Section: Original Articlementioning
confidence: 98%